PERANAN GURU DALAM PENGGUNAAN MULTIMEDIA INTERAKTIF DI ERA REVOLUSI INDUSTRI 4.0 - MZ, Setiawati; Rahmawati, Adi Fatimah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The teacher as an agent of change has a very important role in the success of students in achieving learning goals, especially in the era of industrial revolution 4.0, the use of learning media that are able to create a pleasant learning environment and motivate students to improve their ability to have appropriate competencies with the times, this is where the importance of the role of the teacher as a facilitator in bridging the needs of students for the use of technology that can improve the success of their learning. Learning in this era of revolution 4.0 cannot replace the role of a teacher in the teaching and learning process, but can help teachers and students in achieving educational goals as expected in Undang-Undang Nomor 20 tahun 2003 tentang sistem Pendidikan Nasional, Pasal 3. Interactive multimedia as one of the learning media based on technology is one of several appropriate media to answer the needs of teachers and students in realizing the ideals of national education.